Engineering circuit analysis - Hayt, William Hart (McGraw-Hill Higher Education, 2007)
The hallmark feature of this classic text is its focus on the student - it is written so that students may teach the science of circuit analysis to themselves. Terms are clearly defined when they are introduced, basic material appears toward the beginning of each chapter and is explained carefully and in detail, and numerical examples are used to introduce and suggest general results. Simple practice problems appear throughout each chapter, while more difficult problems appear at the end of each chapter, following the order of presentation of text material. This introduction and resulting repetition provide an important boost to the learning process